Sharia Hotels: Consumer Decisions to Use Hospitality Services Viewed from the Perspective of Prices and Sharia Labels in Medan - Nuri Aslami; Karmila Sinaga (el-Jizya: Jurnal Ekonomi Islam, 2022)
The growth of sharia hotels in the hospitality industry is still foreign to the people of Indonesia, although halal tourism is starting to develop rapidly. One of the sharia hotels in the city of Medan is the Grand Jamee Medan Syariah Hotel. An Acehnese man founded this hotel to provide hospitality that upholds Islamic values. So he decided to use the sharia label. This study aims to determine whether the price and use of sharia labels in the hotel company Syariah Hotel Grand Jamee Medan affect consumer decisions to use hospitality services. Determination of the value is based on the Likert Scale respondents' opinions are given in each answer to the questionnaire. The population used in this study are all consumers who have used the hotel services products of Hotel Syariah Grand Jamee Medan. The number of samples in this study was 30 consumers of Hotel Syariah Grand Jamee Medan. The results of this study indicate that the pricing and use of sharia labels in the hotel company Syariah Hotel Grand Jamee Medan affect consumer decisions in using hospitality services. In the R Square analysis, the number 0.616 means that 61.6% of the dependent variable on consumer decisions to use services can be explained by the independent variable price and sharia label.